Measuring conflict management, emotional self-efficacy, and problem solving confidence in an evaluation of outdoor programs for inner-city youth in Baltimore, Maryland. (August 2016) - Caldas, Stephanie V.; Broaddus, Elena T.; Winch, Peter J.
Highlights: We adapted and piloted three scales for evaluating the effect of brief outdoor education programs on inner-city youth in Baltimore, Maryland. The three scales measure three types of non-cognitive skills: conflict management, emotional self-efficacy and problem solving confidence. The scales were validated through exploratory and confirmatory factor analyses of pilot-testing data from two groups of program participants. These scales can be adapted for routine program monitoring, and enhance accountability by demonstrating if youth are benefiting from the programs as intended. Abstract: Substantial evidence supports the value of outdoor education programs for promoting healthy adolescent development, yet measurement of program outcomes often lacks rigor. Accurately assessing the impacts of programs that seek to promote positive youth development is critical for determining whether youth are benefitting as intended, identifying best practices and areas for improvement, and informing decisions about which programs to invest in. We generated brief, customized instruments for measuring three outcomes among youth participants in Baltimore City Outward Bound programs: conflict management, emotional self-efficacy, and problem solving confidence. Measures were validated through exploratory and confirmatory factor analyses of pilot-testing data from two groups of program participants. We describe our process of identifying outcomes for measurement, developing and adapting measurement instruments, and validating these instruments. The finalized measures support evaluations of outdoor education programs serving urban adolescent youth. Such evaluations enhance accountability by determining if youth are benefiting from programs as intended, and strengthen the case for investment in programs with demonstrated success.